The past as myth. The archaeological (after)life of the Goddess in former Yugoslavia - Merc, Vesna (Monitor ISH, 2007)
Marija Gimbutas's studies have profoundly influenced popular feminism, New Age religions, and Mother Goddess centred movements since the 1970's, but despite the authoress's status of a feminist icon, her influence on popular feminism remains largely unknown in archaeology and her works on Neolithic religion ignored. Modern archaeology, including gender archaeology, is now re-examining her researches and conclusions. The present paper studies how the theory of a Neolithic goddess was received at the time of its emergence and how the social structures of the past were (re)constructed in the archaeologies of former Yugoslavia.
Keywords: archaeology; arheologija; teorija; theory; neolitik; družbena struktura; woman; ženske; boginje; miti; mythology